A BOUNDARY FOR THE EXISTENCE OF SOLUTION TO THE MAXIMUM ENTROPY PROBLEM APPLIED IN EUROPEAN CALL OPTIONS - Margaryan, N.D. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
The following paper introduces a computationally effective way of finding and utilizing maximum entropy problem boundaries for up to three dimensional cases. The application of the results is concentrated on financial options pricing and reverse distribution calculation. Based on market information in form of current option prices a distribution of future states is constructed. Using the suggested approach it will be possible to identify cases, where no solution to the maximum entropy problem exists, and parameters, for which a feasible solution can be reached.
Keywords: boundary; entropy; distribution; options